Mathematical modeling and treating tumors in a fuzzy environment - Aadil Sheergojri; Pervaiz Iqbal (Computational Algorithms and Numerical Dimensions)
To better understand how things work in biology, you can use mathematics to figure things out. Cancer modeling is a complex biological process that is highly unpredictable, which fuzzy models in this study have achieved. Biomolecular components of malignant disorders and their analysis are frequently examined. Even though most documented investigations have not yet reached the competency needed for curing cancer, research has contributed to understanding the statistical principles governing cancer cell development, invasion, and proliferation. This article begins with an overview of mathematical models for tumor development and treatment, which consider stochastic perturbations a therapeutic remedy. Also, it has been demonstrated that fuzzy modeling approaches may be used to investigate the impacts of various components on tumor development estimation, minimize tumor uncertainty, and attain a degree of realism.